Landmarks of Otsego County - Schull, Diantha Dow (Syracuse University Press, 1980)
From Cooperstown to Oneonta, much of the rich architectural heritage of New York State's Otsego County is wonderfully preserved; much of it waits to be explored. Diantha Schull presents more than 200 of the county's eighteenth- and nineteenth-century buildings, sophisticated and simple alike-their styles, uses, histories, preservation, and sometimes their destruction. From great, Romanesque public buildings, classical Greek Revival estates, and fanciful Victorian homes, to one-room schools, octagonal barns, and modest Federal farmhouses, these buildings create a vivid record of the styles, tastes, and necessities of past centuries. Schull sharpens our appreciation for that mix of architecture and history unique to each town or village, its sense of community. Whether used for agriculture, industry, commerce, religion, education, government, or residence, each building is best seen in this holistic context. With hundreds of photographs, a map, and history as a guide, Schull opens our eyes to the architecture of the county, to careful restoration, to adaptive re-use, and to neglect. She encourages us to discover for ourselves the irreplaceable physical heritage around us. Winner of the 1980 John Ben Snow Prize